Development of Cosmetic Product from corn silk extracts - Srisuksomwong, Pawalee; Yucharoen, Raenu (YRU Journal of Science and Technology, 2021)
This research aims to study the performance and optimum concentration of the extracts from corn silk as agricultural waste to inhibit pathogenic bacteria. The growth inhibition of ethyl acetate and water extracts is tested by using agar well diffusion and broth dilution against eight strains bacteria i.e., Serratia marcescens Salmonella typhimurium, Staphylococcus aureus, Escherichia coli, Bacillus cereus, Proteus vulgaris, Pseudomomas aeruginosa and Aeromonas hydrophila. It was found that the water extract of corn silk showed the highest antibacterial activity on B. cereus with inhibition zone of 8.83±1.69 mm. Moreover, the ethyl acetate extract of corn silk showed highest antibacterial activity against S. aureus with inhibition zone of 12.83±3.34 mm, MIC of 62.5 mg/mL and MBC of 125 mg/mL. In addition, corn silk cream provided formulations with good physical and chemical stability. The cream texture was stable without layer. This research is beneficial in promoting effective agricultural waste; corn silk with the use technology and innovation, benefit the community and also raise the standard of Thai cosmetic products and continue to commercial.